Tafsir Tematik Term Ma’shiyah Dan Mushibah Dalam Al-Qur’an - Abdul Rauf Haris; Yazka Muhammad Cholis (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD Cianjur, 2022)
The debate about the relationship between immorality and disaster is important and relevant to be studied, especially during a pandemic. This study aims to describe the relationship between the terms, mushibah and ma’shiyah, from the perspective of the Qur'an by collecting and examining verses containing both terms to understand the logical construction in the Qur'an about the relationship between the two. The research method used is the thematic interpretation of terms. There are 10 verses that contain the term mushibah. There is no verse that simultaneously contains both terms. However, it was found an explanation that one of the causes of the descent of disaster was the human violation of the rules of Allah subhanahu wa ta'ala. This violation itself is a general definition of the term ma'shiyah. The research concludes that there is a causal relationship between the two terms. Based on the perspective of the Qur'an, disaster can come down due to actions that violate Allah's laws or immoral acts. Based on this conclusion, disaster management, in addition to handling physical and material impacts, should be able to encourage each victim to reflect on and get closer to the Creator.